Implementasi Pembelajaran Al-Qur’an dalam Meningkatkan Kemampuan Membaca Al-Qur’an di Konsep R.AQu MAYADA (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study aims to examine the implementation of Qur’anic learning in improving early childhood students’ ability to read the Qur’an, as many young children are still not fluent in Qur’anic reading. The research was conducted at RA Qur’an Mayada. The focus of the study includes: (1) the educational concepts applied by the institution to enhance Qur’anic reading skills, (2) the strategies or programs used in Qur’anic reading instruction, (3) the implementation of Qur’anic learning in improving Qur’anic reading ability, and (4) the inhibiting factors and solutions in strengthening Qur’anic reading proficiency. This study employed a descriptive qualitative method through observation, interviews, and documentation. The results show that the institution develops an integrative curriculum using child-centered learning approaches, particularly through the methods of tilawah, talaqqi, tadarus, and educational games. The main challenges arise from differences in students’ abilities, limited learning time, and unequal family support. Solutions include increasing learning hours, maintaining intensive communication with parents, and providing regular teacher training.